Rare earth magnet and method for manufacturing the same

The method for manufacturing SmFeN-based rare earth magnets by mixing SmFeN magnetic powder with metal zinc or zinc alloys, followed by specific pressurized sintering conditions, effectively addresses the challenge of achieving high density and minimizing magnetic phase distortion, thereby improving the magnetic properties of the magnets.

JP2025066390AActive Publication Date: 2025-04-23TOYOTA JIDOSHA KK +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023175934
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-23
Estimated Expiration
2043-10-11

Smart Images

  • Figure 2025066390000001_ABST
    Figure 2025066390000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a rare earth magnet capable of improving magnetic characteristics by achieving both high densification of a sintered body and suppression of distortion of a magnetic phase.SOLUTION: A method for manufacturing a rare earth magnet includes the steps of: preparing magnetic powder containing Sm, Fe and N; preparing modifier powder containing at least one of metallic zinc and a zinc alloy; obtaining mixed powder by mixing the magnetic powder with the modifier powder; compression-molding the mixed powder in a magnetic field to obtain a magnetic field molded body; and pressure-sintering the magnetic field molded body to obtain a sintered body. In the pressure-sintering, the magnetic field molded body is pressure-sintered at temperature of 360°C or higher and 390°C or lower for a time of one hour or more and 24 hours or less under pressure of 500 MPa or more and 900 MPa or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a rare earth magnet and a rare earth magnet, and more particularly to a method for producing a rare earth magnet in which magnetic powder containing Sm, Fe, and N is sintered, and the rare earth magnet is produced. [Background technology]

[0002] Conventionally, SmCo-based rare earth magnets and NdFeB-based rare earth magnets have been put to practical use as high-performance rare earth magnets, but in recent years, SmFeN-based rare earth magnets containing Sm, Fe, and N have been developed as other rare earth magnets. SmFeN-based rare earth magnets are manufactured using SmFeN-based magnetic powder containing Sm, Fe, and N. As a manufacturing method for SmFeN-based rare earth magnets and rare earth magnets, for example, a manufacturing method for rare earth magnets including mixing SmFeN-based magnetic powder and a modifier powder containing a zinc component to obtain a mixed powder, compression molding the mixed powder in a magnetic field to obtain a magnetic compact, and pressure sintering the magnetic compact to obtain a sintered body, and a rare earth magnet obtained thereby are known (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2023-077289 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the method for manufacturing a rare earth magnet described in Patent Document 1, the SmFeN magnetic powder reacts with the zinc component of the modifier powder during pressure sintering to form a modifier phase on the surface of the magnetic powder, thereby suppressing demagnetization. Furthermore, in order to increase the density of the sintered body in order to improve the magnetic properties, the magnetic compact is pressure sintered at a pressure of 200 MPa to 1500 MPa and a temperature of 300°C to 400°C for 1 minute to 30 minutes during pressure sintering. However, under such conventional pressure sintering conditions, due to the high pressure, distortion may accumulate in the magnetic phase of the sintered body, and the remanent magnetization may not be improved. In addition, due to the high temperature, the SmFeN magnetic powder may react excessively with the zinc component of the modifier powder, which may reduce the proportion of the magnetic phase in the sintered body, and this may result in a decrease in remanent magnetization.

[0005] The present invention has been made in consideration of these points, and its object is to provide a method for manufacturing a rare earth magnet and a rare earth magnet that can improve magnetic properties by achieving both high density of the sintered body and suppression of distortion of the magnetic phase. [Means for solving the problem]

[0006] In order to solve the above problems, the method for manufacturing a rare earth magnet of the present invention includes a step of preparing a magnetic powder containing Sm, Fe, and N (magnetic powder preparation step), a step of preparing a modifier powder containing at least one of metallic zinc and a zinc alloy (modifier powder preparation step), a step of mixing the magnetic powder and the modifier powder to obtain a mixed powder (mixing step), a step of compressing and molding the mixed powder in a magnetic field to obtain a magnetically molded body (magnetic field molding step), and a step of pressure-sintering the magnetically molded body to obtain a sintered body (pressure sintering step), characterized in that in the pressure sintering step, the magnetically molded body is pressure-sintered at a pressure of 500 MPa or more and 900 MPa or less and at a temperature of 360°C or more and 390°C or less for a period of 1 hour to 24 hours.

[0007] In order to solve the above problems, the rare earth magnet of the present invention comprises a sintered body of a mixed powder including a magnetic powder containing Sm, Fe, and N, and a modifier powder containing at least one of metallic zinc and a zinc alloy, the half-width of the diffraction peak of the (024) plane measured by X-ray diffraction of the sintered body being 0.2 degrees or less, and the bulk density of the sintered body being 6.2 g / cm 3 The present invention is characterized in that: Effect of the Invention

[0008] According to the present invention, it is possible to improve the magnetic properties by achieving both high density of the sintered body and suppression of distortion of the magnetic phase. [Brief description of the drawings]

[0009] [Figure 1] 1(a) to 1(c) are schematic process diagrams illustrating a method for producing a rare earth magnet according to one embodiment. [Diagram 2] 1(a) and 1(b) are schematic process diagrams showing a method for producing a rare earth magnet according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] First, an outline of the method for producing a rare earth magnet and the rare earth magnet according to the embodiment will be described by taking one embodiment as an example. Figures 1(a) to 2(b) are schematic process diagrams showing the method for producing a rare earth magnet according to one embodiment.

[0011] In one embodiment of the method for producing a rare earth magnet, first, as shown in FIG. 1(a), coated magnetic powder 4 is prepared (magnetic powder preparation step). The coated magnetic powder 4 includes coated magnetic particles 2 having magnetic particles 2a with a magnetic phase and phosphate coatings 2b covering the surfaces of the magnetic particles 2a. The coated magnetic powder 4 is anisotropic magnetic powder. The magnetic particles 2a contain Sm, Fe, and N. Next, as shown in FIG. 1(b), metal zinc powder 8 including metal zinc particles 6 is prepared as modifier powder 8 (modifier powder preparation step). Next, as shown in FIG. 1(c), the coated magnetic powder 4 and the metal zinc powder 8 are mixed to obtain a mixed powder 10A (mixing step).

[0012] Next, as shown in FIG. 1(d), a molding die 40 and an electromagnetic coil 50 are used to compression mold the mixed powder 10A in a magnetic field (magnetic field molding) to obtain a magnetic field molded body 10B (magnetic field molding process). The molding die 40 includes a die 40A and a punch 40B, the die 40A has a cavity 40C, and the punch 40B slides inside the cavity 40C. The electromagnetic coils 50 are disposed on both sides of the periphery of the die 40A in a direction perpendicular to the sliding direction (direction of the white arrow) of the punch 40B. The magnetic field molding is performed in a nitrogen gas atmosphere. At this time, first, the mixed powder 10A is stored in the cavity 40C of the die 40A in a nitrogen gas atmosphere. Next, the mixed powder 10A is compression-molded by moving the punch 40B while applying a magnetic field from the electromagnetic coil 50 in a direction perpendicular to the sliding direction of the punch 40B (indicated by an arrow) to the mixed powder 10A in the cavity 40C of the die 40A.

[0013] Next, as shown in FIG. 2(a), the magnetic field compact 10B is pressure-sintered using a sintering die 60 and a heater 70 to obtain a sintered body 10C (pressure sintering process). The sintering die 60 includes a die 60A and a punch 60B, the die 60A has a cavity 60C, and the punch 60B slides inside the cavity 60C. The heater 70 includes a high-frequency induction coil 70A arranged around the die 60A in a direction perpendicular to the sliding direction (direction of the white arrow) of the punch 60B. The pressure sintering is performed in an argon gas atmosphere. At this time, the magnetic field compact 10B is first transferred from the die 40A of the molding die 40 into the cavity 60C of the die 60A of the sintering die 60. Next, the magnetic field compact 10B in the cavity 60C of the die 60A is heated by the high frequency induction coil 70A while the punch 60B is moved to pressurize the magnetic field compact 10B. In this manner, the magnetic field compact 10B is pressure sintered at a pressure of 500 MPa to 900 MPa and a temperature of 360°C to 390°C for 1 hour to 24 hours.

[0014] Next, although not shown, the punch 60B of the sintering die 60 is moved to remove the sintered body 10C from the cavity 60C of the die 60A. As a result, as shown in FIG. 2(b), a rare earth magnet 1 including the sintered body 10C is manufactured as a rare earth magnet according to one embodiment. In the rare earth magnet 1, the magnetic particles 2a in the sintered body 10C are bonded by a modifier phase 5 in which the α-Fe phase in the surface portion is alloyed with the zinc component of the modifier powder 8. In the X-ray diffraction pattern measured by X-ray diffraction of the surface of the sintered body 10C, the half-width of the diffraction peak of the (024) plane of the crystal structure of the magnetic phase of the magnetic particles 2a of the sintered body 10C is 0.2 degrees or less. The bulk density of the sintered body 10C is 6.2 g / cm 3 That's all.

[0015] In one embodiment of the method for producing a rare earth magnet, in the pressure sintering step, the magnetically compacted body is pressure sintered at a pressure of 500 MPa to 900 MPa and a temperature of 360° C. to 390° C. for a period of 1 hour to 24 hours. In this way, by performing pressure sintering under conditions of lower pressure and longer time than conventional, the bulk density of the sintered body is increased to 6.2 g / cm. 3 The above can be achieved, and the half-width of the diffraction peak of the (024) plane of the crystal structure of the magnetic phase of the magnetic particles of the sintered body can be reduced to 0.2 degrees or less. In other words, it is possible to achieve both high density of the sintered body of the rare earth magnet according to one embodiment and suppression of distortion of the magnetic phase. This makes it possible to improve the magnetic properties such as residual magnetization of the rare earth magnet according to one embodiment. Next, the manufacturing method of the rare earth magnet and the rare earth magnet according to the embodiment will be described in detail.

[0016] 1. Manufacturing method of rare earth magnets The method for producing a rare earth magnet includes a magnetic powder preparation step, a modifier powder preparation step, a mixing step, a magnetic field compaction step, and a pressure sintering step.

[0017] (1)Magnetic powder preparation process In the magnetic powder preparation step, a magnetic powder containing Sm, Fe, and N (hereinafter, sometimes abbreviated as "SmFeN magnetic powder" or "magnetic powder") is prepared. The SmFeN magnetic powder is not particularly limited as long as it has a magnetic phase and contains magnetic particles containing Sm, Fe, and N. The SmFeN magnetic powder may be a general one, but is usually an anisotropic magnetic powder. The SmFeN magnetic powder may be, for example, an uncoated magnetic powder in which the surfaces of the magnetic particles are not covered with a phosphate coating, or a coated magnetic powder containing coated magnetic particles having magnetic particles and a phosphate coating covering the surfaces of the magnetic particles. As the SmFeN magnetic powder, a coated magnetic powder is preferable. This is because the phosphate coating can suppress the deterioration of the magnetic particles due to oxidation during the magnet manufacturing process.

[0018] The magnetic phase of the magnetic particles of the magnetic powder is not particularly limited as long as it contains Sm, Fe, and N, and may be a general one. 17Type and Th2Ni 17 The magnetic phase is a phase having at least one of the crystal structures of the TbCu7 type. The magnetic phase is not particularly limited, but may further include a phase having a TbCu7 type crystal structure. Sm is samarium, Fe is iron, and N is nitrogen. Th is thorium, Zn is zinc, Ni is nickel, Tb is terbium, and Cu is copper. Rare earth magnets exhibit magnetization due to the magnetic phase of the magnetic particles of the magnetic powder.

[0019] The magnetic particles of the magnetic powder are not particularly limited as long as they have the magnetic phase as described above and contain Sm, Fe, and N, and may have a general composition. For example, in addition to Sm, Fe, and N, particles that further contain one or more elements selected from the group consisting of La, W, and R (R is at least one selected from the group consisting of Ti, Ba, Sr, and Co) are included, and among these, particles whose composition is represented by the following general formula (1) are preferred.

[0020] Sm v Fe (100-v―w-x-y-z) N w La x W y R z (1) (The subscripts v, w, x, y, and z in the formula satisfy the conditions: 3≦v≦30, 3≦w≦15, 0≦x≦0.5, 0≦y≦2.5, and 0≦z≦0.3.)

[0021] In the above general formula (1), v is specified to be 3 or more and 30 or less because if v is less than 3, the unreacted portion of the iron component (α-Fe phase) may separate, decreasing the coercive force of the magnetic powder. If v exceeds 30, the element Sm may precipitate, making the magnetic powder unstable in the air and decreasing the remanent magnetization. If w is specified to be 3 or more and 15 or less, if w is less than 3, almost no coercive force may be exhibited, and if w exceeds 15, there is a risk of nitrides of Sm or iron itself being formed. x is 0 or more and 0.5 or less, but preferably 0.05 or more and 0.5 or less. If x is less than 0.05, the effect of the addition is insufficient, and if x exceeds 0.5, there is a risk of nitrides of Sm or iron itself being formed, decreasing the magnetization. y is 0 or more and 2.5 or less, but preferably 0.05 or more and 2.5 or less. If y is less than 0.05, the effect of the addition is insufficient, and if y exceeds 2.5, nitrides of Sm and iron themselves may be formed, which may result in a decrease in magnetization. z is 0 or more and 0.3 or less, and preferably 0.0001 or more and 0.3 or less. If z is less than 0.0001, the effect of the addition is insufficient, and nitrides of Sm and iron themselves may be formed, which may result in a decrease in magnetization.

[0022] The content of Sm in the magnetic particles of the magnetic powder is, for example, preferably 3% by mass or more and 30% by mass or less, and more preferably 20% by mass or more and 25% by mass or less. The content of N in the magnetic particles of the magnetic powder is, for example, preferably 3% by mass or more and 15% by mass or less, and more preferably 3.3% by mass or more and 3.5% by mass or less. If the content of N is too high, over-nitriding occurs, and if the content of N is too low, nitriding occurs insufficiently, and the magnetic properties tend to deteriorate. The content of Fe in the magnetic particles of the magnetic powder is the amount obtained by subtracting the content of elements other than Fe from the content of all elements contained in the magnetic particles of the magnetic powder.

[0023] When the magnetic particles of the magnetic powder further contain La, the La content is preferably 0.1% by mass or more and 5% by mass or less, for example, from the viewpoint of residual magnetization, and more preferably 0.15% by mass or more and 1% by mass or less. When the magnetic particles of the magnetic powder further contain W, the W content is preferably 0.1% by mass or more and 5% by mass or less, for example, from the viewpoint of coercivity, and more preferably 0.15% by mass or more and 1% by mass or less. When the magnetic particles of the magnetic powder further contain R, the R content is preferably 1.0% by mass or less, for example, from the viewpoint of temperature characteristics, and more preferably 0.5% by mass or less.

[0024] Cumulative 50% particle size D in the volumetric particle size distribution of magnetic powder 50 The (median diameter) is not particularly limited and may be a general one, but when the magnetic powder is a coated magnetic powder, it is preferably, for example, from 2 μm to 5 μm, and more preferably from 2.5 μm to 4.5 μm. 50 If D is too small, the amount of magnetic powder packed in the magnet will be small, and magnetization may decrease. 50 If is too large, the coercive force of the magnet tends to decrease. 50 Also, when the magnetic powder is a coated magnetic powder, the D 50 The same applies to the magnetic powder D 50 can be determined, for example, by measurement using a laser diffraction particle size distribution measuring device.

[0025] The coated magnetic powder is obtained by phosphoric acid treatment of a magnetic powder including magnetic particles having a magnetic phase containing Sm, Fe, and N. By phosphoric acid treatment of the magnetic powder, a phosphoric acid coating, which is a passive film having a PO bond, is formed on the surface of the magnetic particles of the magnetic powder. In the phosphoric acid treatment, the magnetic powder is reacted with a phosphoric acid treatment agent such as a phosphate salt such as orthophosphoric acid. In this case, a method of putting the magnetic powder into a phosphoric acid solution in which the phosphoric acid treatment agent is dissolved in water or an organic solvent is used. In addition, when the magnetic powder is phosphoric acid treated, it is preferable to dry the magnetic powder under normal pressure or under vacuum after the phosphoric acid treatment. This is because the coercive force of the magnet can be improved by chemically bonding the phosphoric acid coating to the magnetic particles. In addition, the drying temperature is preferably 140°C or higher. The thickness of the phosphoric acid coating is not particularly limited and may be a general thickness. The thickness of the phosphoric acid coating is, for example, 1 nm to 50 nm, and preferably 5 nm to 30 nm.

[0026] (2) Modifier powder preparation process In the modifier powder preparation step, modifier powder containing at least one of metallic zinc and a zinc alloy is prepared. The modifier powder modifies and bonds the magnetic particles of the magnetic powder with the zinc component.

[0027] The modifier powder is not particularly limited as long as it is the above-mentioned powder, and may be a general modifier powder. For example, the modifier powder may be a metal zinc powder containing metal zinc particles, or a zinc alloy powder containing zinc alloy particles.

[0028] Zinc alloys are made by dissolving Zn in another element (M 2 ) alloyed with Zn-M 2 "), where Zn is zinc, M is 2 is another element other than zinc. 2 There are no particular limitations on the M element, so long as it can be alloyed with Zn, and any common element will do. 2As the melting point lowering element, for example, one or more elements selected from elements that lower the melting start temperature of the zinc alloy below the melting point of Zn (hereinafter, sometimes abbreviated as "melting point lowering elements"), inevitable impurity elements, etc. are preferable. This is because it improves the sintering property during pressure sintering. As the melting point lowering element, for example, an element that can form a eutectic alloy with Zn can be mentioned, and specifically, one or more elements such as Sn, Mg, Al, etc. can be mentioned. Sn is tin, Mg is magnesium, and Al is aluminum. Note that M 2 The modifier may further contain one or more elements that do not impair the melting point lowering effect of the melting point lowering element or the properties of the magnet, in addition to the melting point lowering element and unavoidable impurity element. An unavoidable impurity element means an impurity element that cannot be avoided from being contained in the modifier powder, such as an impurity contained in the raw material of the modifier powder, as well as an impurity element that requires a significant cost to avoid being contained in the modifier powder. Zn-M 2 Zn and M in 2 The molar ratio of Zn-M is not particularly limited and may be a general molar ratio, and may be appropriately determined so that the sintering temperature during pressure sintering is appropriate. 2 M in 2 The molar ratio of Zn-M is, for example, 0.05 or more, preferably 0.10 or more, and more preferably 0.20 or more. 2 M in 2 The molar ratio is, for example, 0.90 or less, and is preferably 0.80 or less, particularly preferably 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less.

[0029] The total content of metallic zinc and zinc alloy in the modifier powder is not particularly limited and may be a general content, for example, 90% by mass or more and 100% by mass or less, and preferably 95% by mass or more and 100% by mass or less. In addition to metallic zinc and zinc alloy, the modifier powder may optionally contain at least one of a binder function, a modifier function, and other functions (such as a function of improving corrosion resistance) as long as the effect of the present invention is not impaired. The content of such a substance in the modifier powder is, for example, the content of the portion excluding metallic zinc and zinc alloy from the entire modifier powder.

[0030] Cumulative 50% particle size D in the volumetric particle size distribution of modifier powder 50 The (median diameter) is not particularly limited, but is, for example, 0.1 μm or more, preferably 0.5 μm or more, and particularly preferably 1 μm or more. 50 For example, the D of the modifier powder is preferably 4 μm or less, more preferably 2 μm or less, and particularly preferably 1 μm or less. 50 can be determined, for example, by measurement using a laser diffraction particle size distribution measuring device.

[0031] (3) Mixing process In the mixing step, the magnetic powder and the modifier powder are mixed to obtain a mixed powder. The content of the modifier powder in the mixed powder is not particularly limited and may be a general content, but from the viewpoint of residual magnetization, for example, it is preferable that the content is 2 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the SmFeN magnetic powder, and particularly, it is preferable that the content is 5 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the SmFeN magnetic powder.

[0032] The method for mixing the magnetic powder and modifier powder is not particularly limited and may be a common method, for example, a mortar, a Muller wheel mixer, an agitator mixer, Mechanofusion, a V-type mixer, a ball mill, etc.

[0033] (4) Magnetic field forming process In the magnetic field compaction process, the mixed powder is compressed and molded in a magnetic field (hereinafter sometimes abbreviated as "magnetic field compaction") to obtain a magnetic field compact. The magnetic field compact is given orientation. This gives anisotropy to the rare earth magnet and improves remanence.

[0034] The method of magnetic field molding is not particularly limited, and may be a general method, but examples thereof include a method of compressing the mixed powder in a mold while applying a magnetic field to the mixed powder with a magnetic field generator arranged around a mold such as a metal mold. Examples of the magnetic field generator include a device such as an electromagnetic coil that applies a static magnetic field, and a device that applies a pulse magnetic field using an alternating current. The atmosphere in which the magnetic field molding is performed is not particularly limited, but an inert gas atmosphere such as an argon gas atmosphere or a nitrogen gas atmosphere is preferable. This is because oxidation of the magnetic field molded body can be suppressed. The molding pressure of the magnetic field molding is, for example, 10 MPa or more, preferably 20 MPa or more, particularly preferably 30 MPa or more, 50 MPa or more, or 100 MPa or more. The molding pressure is, for example, 1500 MPa or less, preferably 1000 MPa or less, particularly preferably 500 MPa or less, 200 MPa or less, or 100 MPa or less. The application time of the molding pressure is, for example, 0.5 minutes or more, preferably 1 minute or more, particularly preferably 3 minutes or more. The application time of the molding pressure is, for example, 10 minutes or less, preferably 7 minutes or less, and particularly preferably 5 minutes or less. The strength of the magnetic field in the magnetic field molding is, for example, 500 kA / m or more, preferably 1000 kA / m or more, particularly preferably 1500 kA / m or more, 1600 kA / m or more. The strength of the magnetic field is, for example, 20000 kA / m or less, preferably 15000 kA / m or less, particularly preferably 10000 kA / m or less, 5000 kA / m or less, 3000 kA / m or less, 2000 kA / m or less.

[0035] (5) Pressure sintering process In the pressure sintering step, the magnetic field compact is pressure sintered (hereinafter, sometimes abbreviated as "pressure sintering") to obtain a sintered body. The pressure sintering method is not particularly limited and may be a general method, for example, a method in which the magnetic field compact is heated by a heating device while being pressurized by a molding die such as a metal mold. An example of the heating device is a heater equipped with a high-frequency induction coil arranged around the molding die. The atmosphere in which the pressure sintering is performed is not particularly limited, but an inert gas atmosphere such as an argon gas atmosphere or a nitrogen gas atmosphere is preferable. This is because oxidation of the sintered body can be suppressed.

[0036] In the pressure sintering, the magnetic compact is pressure sintered at a pressure of 500 MPa to 900 MPa and a temperature of 360° C. to 390° C. for 1 hour to 24 hours. This makes it possible to simultaneously increase the density of the sintered rare earth magnet and suppress distortion of the magnetic phase.

[0037] When the pressure of the pressure sintering is 500 MPa or more and 900 MPa or less, the sintered body can be densified and the distortion of the magnetic phase can be suppressed. When the temperature of the pressure sintering is 360 ° C or more and 390 ° C or less, the α-Fe phase on the surface of the magnetic particles and the zinc component of the modifier powder on the surface of the magnetic particles are alloyed to form a modifier phase, which is an Fe-Zn alloy phase, and demagnetization can be suppressed. In addition, the sintered body can be densified and the distortion of the magnetic phase can be suppressed. When the temperature is less than 360 ° C, the modifier phase may not be formed. When the temperature exceeds 390 ° C, the magnetic powder and the zinc component of the modifier powder react excessively, reducing the proportion of the magnetic phase in the sintered body and increasing the distortion of the magnetic phase. In addition, various phases such as alloy phases and α-Fe phases other than the modifier phase are generated on the surface of the magnetic particles, causing demagnetization. When the pressure sintering time is 1 hour or more and 24 hours or less, the sintered body can be densified and the distortion of the magnetic phase can be suppressed. When the time is less than 1 hour, the sintered body may not be densified.

[0038] (6) Manufacturing method of rare earth magnets The method for producing a rare earth magnet is not particularly limited as long as it includes the above steps, but for example, a preferred method is one in which the magnetic powder is a coated magnetic powder including coated magnetic particles having magnetic particles with a magnetic phase containing Sm, Fe, and N and a phosphate coating covering the surfaces of the magnetic particles, the modifier powder is metallic zinc powder, and the content of the modifier powder in the mixed powder is 5 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the magnetic powder. The half-width of the diffraction peak of the (024) plane measured by X-ray diffraction of the sintered body is 0.2 degrees or less, and the bulk density of the sintered body is 6.2 g / cm. 3In other words, it is easy to achieve both high density of the sintered rare earth magnet and suppression of distortion of the magnetic phase. A method for producing a rare earth magnet includes, for example, setting the cumulative 50% particle size D 50 is 2 μm or more and 5 μm or less, and the cumulative 50% particle size D in the volume-based particle size distribution of the modifier powder is 50 A method in which the average particle size is 0.1 μm or more and 4 μm or less is preferable, because this makes it easy to achieve both high density sintered rare earth magnets and suppression of distortion of the magnetic phase.

[0039] 2.Rare earth magnets The rare earth magnet comprises a sintered body of a mixed powder including a magnetic powder containing Sm, Fe, and N, and a modifier powder containing at least one of metallic zinc and a zinc alloy, the half-width of the diffraction peak of the (024) plane of the sintered body measured by X-ray diffraction is 0.2 degrees or less, and the bulk density of the sintered body is 6.2 g / cm. 3 The rare earth magnet is not particularly limited as long as it is one of the above rare earth magnets, but it is preferable to use one manufactured by the method for manufacturing a rare earth magnet described above in "1. Manufacturing method of a rare earth magnet".

[0040] The magnetic powder contained in the mixed powder used for the sintered rare earth magnet is the same as the SmFeN magnetic powder described in "1. Manufacturing method of rare earth magnet (1) Magnetic powder preparation step" above. The modifier powder contained in the mixed powder is the same as the modifier powder described in "1. Manufacturing method of rare earth magnet (2) Modifier powder preparation step" above. The mixed powder is the same as the mixed powder described in "1. Manufacturing method of rare earth magnet (3) Mixing step" above. The sintered rare earth magnet is not particularly limited as long as it is the above sintered body, but for example, a sintered body of a magnetic field compact of the mixed powder is preferable. EXAMPLES

[0041] The method for producing a rare earth magnet and the rare earth magnet according to the embodiment will be described in more detail below with reference to examples and comparative examples.

[0042] [Example 1] An example of a method for manufacturing a rare earth magnet according to one embodiment of the present invention was carried out. First, a coated magnetic powder was prepared (magnetic powder preparation process). The coated magnetic powder includes coated magnetic particles having magnetic particles with a magnetic phase and a phosphoric acid coating covering the surface of the magnetic particles. The magnetic particles contain Sm (22.3 mass%), Fe (71.5 mass%), N (3.3 mass%), La (0.48 mass%), W (0.51 mass%), and Ti (0.17 mass%). The coated magnetic powder was obtained by phosphoric acid treatment of a magnetic powder including magnetic particles. In the phosphoric acid treatment in this case, first, the magnetic powder was put into pure water to obtain a slurry, and then a phosphoric acid solution was put into the slurry so that PO4 of phosphoric acid (H3PO4) was added at 1 mass% relative to the magnetic particle solid content. Next, the slurry was stirred for 5 minutes, solid-liquid separation was performed, and then vacuum drying was performed at 190°C for 3 hours. As a result, a phosphoric acid coating, which is a passive film having a PO bond, was formed on the surface of the magnetic particles. D of coated magnetic powder 50 was 3.00 μm.

[0043] Next, as the modifier powder, a metal zinc powder containing metal zinc particles (metal zinc purity: 99.9 mass%, D 50 A modifier powder preparation step was performed. Next, the coated magnetic powder and the metal zinc powder were mixed so that the content of the metal zinc powder was 7.5 mass %, and the coated magnetic powder and the metal zinc powder were mixed using a vibration mill to obtain a mixed powder (mixing step).

[0044] Next, the mixed powder was compression molded in a magnetic field (magnetic field molding) to obtain a magnetic field compact (magnetic field molding process). Magnetic field molding was performed in a nitrogen gas atmosphere, with the molding pressure of the magnetic field molding being 50 MPa, the application time of the molding pressure of the magnetic field molding being 1 minute, and the strength of the magnetic field of the magnetic field molding being 1600 kA / m. The magnetic field orientation in the magnetic field molding aligns the easy magnetization axis of the magnetic particles of the magnetic field compact.

[0045] Next, the magnetic compact was pressure sintered to obtain a sintered body (pressure sintering process). Pressure sintering was performed in an argon gas atmosphere of 97,000 Pa, with a pressure (press pressure) of 900 MPa, a pressure sintering temperature (press temperature) of 390°C, and a pressure sintering time (press time) of 24 hours. In this manner, a rare earth magnet comprising a sintered body was manufactured. The manufacturing conditions, including the composition of the mixed powder and the pressure sintering conditions, are shown in Table 1 below.

[0046] [Examples 2 to 4 and Comparative Examples 1 to 9] The pressure, temperature and time for pressure sintering were as shown in the following Table 1. Except for this, a rare earth magnet comprising a sintered body was produced in the same manner as in Example 1.

[0047] [Evaluation of the half-width of the diffraction peak of the (024) plane of the sintered body] X-ray diffraction measurements were performed on the surface perpendicular to the easy axis of magnetization of the rare earth magnet sintered body of each of Examples 1 to 4 and Comparative Examples 1 to 9, and the X-ray diffraction patterns were measured. The measurements were performed under conditions of an inert atmosphere using CuKα radiation. From the X-ray diffraction patterns, the half-width [degrees] of the diffraction peak of the (024) plane of the crystal structure of the magnetic phase of the magnetic particles of the sintered body was obtained. The results are shown in Table 1 below.

[0048] [Bulk density evaluation] The weight and volume of the sintered rare earth magnet of each of Examples 1 to 4 and Comparative Examples 1 to 9 were measured. The bulk density [g / cm 3 The results are shown in Table 1 below.

[0049] [Evaluation of magnetic properties] The magnetic properties of the rare earth magnets of Examples 1 to 4 and Comparative Examples 1 to 9 were evaluated. At this time, the rare earth magnets of each example were pulse magnetized at room temperature with a magnetizing magnetic field of 6400 kA / m, and the residual magnetization Br [T] was measured using a VSM (vibrating sample magnetometer) with a maximum magnetic field of 1600 kA / m. The results are shown in Table 1 below.

[0050] [Table 1]

[0051] [Consideration] As shown in Table 1 above, in Examples 1 to 4, the manufacturing conditions for the rare earth magnets were a pressure (press pressure) of 500 MPa to 900 MPa, a pressure (press temperature) of 360°C to 390°C, and a time (press time) of 1 hour to 24 hours. As a result, the rare earth magnets were evaluated to have a bulk density of 6.2 g / cm 3 As a result, the half-width of the diffraction peak of the (024) plane of the crystal structure of the magnetic phase of the sintered body was 0.2 degrees or less. As a result, the remanent magnetization Br was 0.9 T or more.

[0052] On the other hand, in Comparative Examples 1 and 2, the half-width exceeded 0.2 degrees. This is believed to be because the pressure exceeded 900 MPa, which caused the deformation of the magnetic particles to increase and reduced the crystallinity of the magnetic phase. In Comparative Examples 3 and 4, the bulk density was 6.2 g / cm 3 . This is believed to be because the pressure was less than 500 MPa and the sintered body could not be made dense. In Comparative Example 5, the half-width exceeded 0.2 degrees. This is believed to be because the temperature exceeded 390°C, which caused the deformation of the magnetic particles to increase and reduced the crystallinity of the magnetic phase. In Comparative Example 6, the half-width exceeded 0.2 degrees. This is believed to be because the pressure was 900 MPa and the temperature was less than 360°C, which maintained the hardness of the magnetic particles and increased the pressing force between the magnetic particles, resulting in reduced crystallinity of the magnetic phase. In Comparative Example 7, the half-width exceeded 0.2 degrees. This is believed to be because the temperature exceeded 390°C, which caused an excessive reaction between the magnetic powder and the zinc component and increased distortion of the magnetic phase. In Comparative Example 8, the bulk density was 6.2 g / cm 3 The half-width was below 0.2 degrees. This is believed to be because the sintered body could not be densified due to the temperature being less than 360°C under the pressure of 500 MPa. In Comparative Example 9, the half-width exceeded 0.2 degrees. This is believed to be because the time exceeded 24 hours, which caused the deformation of the magnetic particles to increase and reduced the crystallinity of the magnetic phase.

[0053] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to the above-described embodiments, and various design modifications can be made without departing from the spirit of the present invention as described in the claims. [Explanation of symbols]

[0054] 1: rare earth magnet, 2: coated magnetic particles, 2a: magnetic particles, 2b: phosphate coating, 4: coated magnetic powder, 5: modifier phase, 6: metallic zinc particles, 8: metallic zinc powder (modifier powder), 10A: mixed powder, 10B: magnetic field compact, 10C: sintered body

Claims

1. Preparing a magnetic powder containing Sm, Fe, and N; preparing a modifier powder containing at least one of metallic zinc and a zinc alloy; mixing the magnetic powder and the modifier powder to obtain a mixed powder; A step of obtaining a magnetically compacted body by compression molding the mixed powder in a magnetic field; and obtaining a sintered body by pressure sintering the magnetic field compact. The pressure sintering step comprises pressure sintering the magnetic compact at a pressure of 500 MPa to 900 MPa and a temperature of 360°C to 390°C for 1 hour to 24 hours.

2. The magnetic material has a sintered body of a mixed powder including a magnetic powder containing Sm, Fe, and N, and a modifier powder containing at least one of metallic zinc and a zinc alloy, The half-width of the diffraction peak of the (024) plane measured by X-ray diffraction of the sintered body is 0.2 degrees or less, The bulk density of the sintered body is 6.2 g / cm 3 A rare earth magnet characterized by the above.

Citation Information

Patent Citations

  • Method for producing rare earth magnet

    JP2020155545A

  • Method for producing rare earth magnet

    JP2020155740A

  • Manufacturing method of rare earth magnet

    JP2023151499A

  • Rare earth magnet and manufacturing method thereof

    JP2023077289A